2022
DOI: 10.3390/antibiotics11081118
|View full text |Cite
|
Sign up to set email alerts
|

Resistance towards Critically Important Antimicrobials among Enterococcus faecalis and E. faecium in Poultry Farm Environments in Selangor, Malaysia

Abstract: Multidrug resistant (MDR) enterococci pose significant public health challenges. However, the extent of resistance in the environment is less explored. This study aimed to determine the antibiotic resistance in a poultry farm environment. Eighty enterococcal isolates recovered from the soil and effluent water of 28 poultry farms in Selangor state were included in the study for further bacterial identification and antibiotic susceptibility testing using a VITEK 2 system. Data were analyzed using Statistical Pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Chow [34] stated that all the enterococci tested exhibited a modest inherent resistance to aminoglycosides, including gentamicin, which was regarded as the most often recommended aminoglycoside for enterococci infections. Comparable observations by Maschieto et al [35], Rajendiran et al [36], and Wei et al [37] revealed a moderate level of resistance to streptomycin. sistance (18.18%) regarding the E. faecium strains; the maximum resistance rate (100%) was seen for tetracycline and erythromycin, while the lowest resistance rate (12.5%) was observed for streptomycin (Figure 1B).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Chow [34] stated that all the enterococci tested exhibited a modest inherent resistance to aminoglycosides, including gentamicin, which was regarded as the most often recommended aminoglycoside for enterococci infections. Comparable observations by Maschieto et al [35], Rajendiran et al [36], and Wei et al [37] revealed a moderate level of resistance to streptomycin. sistance (18.18%) regarding the E. faecium strains; the maximum resistance rate (100%) was seen for tetracycline and erythromycin, while the lowest resistance rate (12.5%) was observed for streptomycin (Figure 1B).…”
Section: Resultsmentioning
confidence: 63%
“…Chow [34] stated that all the enterococci tested exhibited a modest inherent resistance to aminoglycosides, including gentamicin, which was regarded as the most often recommended aminoglycoside for enterococci infections. Comparable observations by Maschieto et al [35], Rajendiran et al [36], and Wei et al [37] revealed a moderate level of resistance to streptomycin. MDR Enterococcus sp.…”
Section: Resultsmentioning
confidence: 63%
“…In particular, the ability to cause infection is critical to avoid the action of most commonly used antimicrobials. Recently, antimicrobial-resistant enterococci isolated from poultry farms have become a problem in many countries, including Korea (34)(35)(36)(37), because antimicrobialresistant enterococci can easily spread within pathogenic strains or between pathogenic and non-pathogenic strains (38). Moreover, resistance to fluoroquinolones, which are critically important in human medicine, has been continuously reported worldwide (39).…”
Section: Discussionmentioning
confidence: 99%
“…The rise in antibiotic resistance among Enterococcus species, particularly E. faecalis, underscores the urgent need for the development of new anti-infective therapies [6][7][8]. The surge in antibiotic-resistant E. faecalis strains has increased the urgency for innovative therapeutic approaches, prompting keen interest in phage-based interventions [9][10][11]. This burgeoning interest stems from the demonstrated efficacy of phage therapy (PT) in exerting lytic activity against diverse antibiotic-resistant E. faecalis isolates [12][13][14], thus providing a promising alternative treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…The surge in antibiotic-resistant E . faecalis strains has increased the urgency for innovative therapeutic approaches, prompting keen interest in phage-based interventions [ 9 11 ]. This burgeoning interest stems from the demonstrated efficacy of phage therapy (PT) in exerting lytic activity against diverse antibiotic-resistant E .…”
Section: Introductionmentioning
confidence: 99%